Other people's lives, other people's livelihoods – making ALARP decisions in the context of considerations other than safety and cost. Issue 4 (1st October 2016) - Stephens, David W.
Abstract: Safety legislation and standards in the UK and elsewhere require risks to be reduced 'as low as reasonably practicable' (ALARP). Case law defines ALARP as a level of safety that could not be reduced without sacrifice that is grossly disproportionate to the reduction in risk that is achieved. It is conventionally seen in terms of weighing safety improvements against costs, with a transparent bias on the side of health and safety. However, ALARP decisions are often made in the context of other values as well, such as environmental, social or community impacts. Adequate treatment of the resulting three- or four-way decisions requires recognition that the issues go beyond technical and economic calculations or literal interpretation of legislation and consideration of the ethical issues that underlie the ALARP principle. Unfortunately, the ethical principles most commonly applied in ALARP decision making – equity and utility – are insufficient to guide such decisions. This paper, therefore, turns to an older principle that combines a general concern for the welfare of our neighbours with a particular concern for the vulnerable. This 'neighbourly' approach may be used to guide decisions consistently with the ALARP principle in cases where issues beyond safety and cost must be taken into account. Three hypothetical examples, based on real projects, are used to illustrate how framing the ALARP decision in terms of impacts on neighbours may be used to reach decisions that are consistent and transparent and hence likely to be robust in the face of public challenge.